Absorbed dose estimates from a single measurement one to three days after the administration of 177Lu-DOTATATE/-TOC - Hänscheid, Heribert; Lapa, Constantin; Buck, Andreas K.; Lassmann, Michael; Werner, Rudolf A. (Nuklearmedizin - NuclearMedicine, 2017)
Aim: To retrospectively analyze the accuracy of absorbed dose estimates from a single measurement of the activity concentrations in tumors and relevant organs one to three days after the administration of 177Lu-DOTA-TATE/TOC assuming tissue specific effective half-lives. Methods: Activity kinetics in 54 kidneys, 30 neuroendocrine tumor lesions, 25 livers, and 27 spleens were deduced from series of planar images in 29 patients. After adaptation of mono- or bi-exponential fit functions to the measured data, it was analyzed for each fit function how precise the time integral can be estimated from fixed tissue-specific half-lives and a single measurement at 24, 48, or 72 h after the administration. Results: For the kidneys, assuming a fixed tissue-specific half-life of 50 h, the deviations of the estimate from the actual integral were median (5 % percentile, 95 % percentile): -3 °% (-15 %>; +16 °%) for measurements after 24 h, +2 %> (-9 %>; +12 %>) for measurements after 48 h, and 0 % (-2 %; +12 %) for measurements after 72 h. The corresponding values for the other tissues, assuming fixed tissue-specific half-lives of 67 h for liver and spleen and 77 h for tumors, were +2 % (-25 %; +20 %) for measurements after 24 h, +2 °% (-16 %>; +17 %>) for measurements after 48 h, and +2 %> (-11 %>; +10 %>) for measurements after 72 h. Conclusions: Especially for the kidneys, which often represent the dose limiting organ, but also for liver, spleen, and neuroendocrine tumors, a meaningful absorbed dose estimate is possible from a single measurement after 2, more preferably 3 days after the administration of 177Lu-DOTA-TATE/-TOC assuming fixed tissue specific effective half-lives.
Keywords: PRRT; neuroendocrine tumors; 177Lu; dosimetry